Recycling Edwardian Geology Excursions for Five Modern Cyclists’ Geotrails in England - Thomas Hose (Geoconservation Research)
Around the 1900s, the Geologists’ Association offered a few excursions, although most were for pedestrians, for cyclists. At that time the London-based Geologists’ Association was well placed to employ the railway network to transport its members to and from excursion areas; locations immediately north of London (especially in the counties of Bedfordshire, Buckinghamshire and Hertfordshire) were particularly favored due to their regular trains. Its excursions were advertised in its Monthly Circular and usually later reported in its Proceedings; both now provide sufficient information to recreate and contextualize the cycling and other excursions as modern cyclists’ geotrails. The original excursions were offered at a time when leisure cycling was booming, the ‘Edwardian period’ which is noteworthy as one of major political, social and technological changes. The impact of these changes is evident today, and linking modern geotrails to the Edwardian background can make them attractive to non-specialist users and encourage their engagement with geology, particularly economic geology. Five new cyclists’ geotrails, based upon ‘Edwardian period’ excursions and their socio-political and technological background, have been published and these are contextualized, analyzed and examined as models for similar future provision.